Treatment Onset and Epilepsy Prognosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The efficacy of treatment in relation to the lost time "tiempo perdido" in a group of 3529 epileptic patients was evaluated in the Division of Neurology and Clinical Neurophysiology, Hospital General du Cataluna, Barcelona, Spain.